2017
DOI: 10.1002/lary.26861
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal exposure and margin status in glottic cancer treated by transoral laser microsurgery

Abstract: 2b. Laryngoscope, 128:1146-1151, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…The AC is the laryngeal subsite closest to this interface, and so this might lead to a poorer coverage of the prescribed dose in that subsite . As for TLM, laryngeal exposure is one of the most important factors affecting the outcomes of glottic cancer . In other words, the worse the exposure, the greater the risk of negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The AC is the laryngeal subsite closest to this interface, and so this might lead to a poorer coverage of the prescribed dose in that subsite . As for TLM, laryngeal exposure is one of the most important factors affecting the outcomes of glottic cancer . In other words, the worse the exposure, the greater the risk of negative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, its systematic application to the preoperative assessment of patients to be submitted to TLM was shown to be important in avoiding inadequate surgical margins after such a surgical approach. In fact, when considering glottic cancer, surgical outcomes were shown to be poorer in patients with suboptimal exposure than in those having good visualization of the target itself . In particular, Piazza et al demonstrated a significantly increased rate of positive surgical margins (47.4% vs. 19.2%, P = 0.001) in patients with class II to III exposure rather than with class 0 to I when treated by TLM for early‐intermediate glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of exposure guides the surgeon's decision to propose a transoral or external approach. The basis for performing a safe transoral surgery is adequate exposure of the area to be treated to minimize the risk of damage to surrounding tissue or incomplete resection, which is especially important in oncologic surgery. For transoral robotic surgery, some authors have proposed preoperative anatomic variables or cephalometric measures taken from the imaging to help select patients suitable for the procedure and to reduce the risk of intraoperative conversion to open surgery.…”
Section: Discussionmentioning
confidence: 99%